Dari “Ya” Menjadi “Tidak” Studi tentang Persepsi dan Sikap Masyarakat Desa Idamdehe terhadap Rencana Pembangunan PLTP di Idamdehe dan Idamdehe Gamsungi - Djumaty, Brian L (KRITIS, 2016)
Idamdehe is a village in the province of North Maluku with the potential of geothermal energy to be used for electric power. The central (government) and local government plan to develop the geothermal energy. The preparation was conducted between 2009-2012. This study aimed to describe and analyze the perceptions and attitudes of rural community in Idamdehe to geothermal energy development plan. The method used is qualitative, using data collection techniques like interviews, observation and document study. This research shows that a number of community members agreed to this plan for some reason. Those are poverty, human factors and socio-cultural factors. At the beginning the majority of people agree on the implementation of geothermal energy development plan. However, a small group in the community did not agree while others didn’t have any opinion. After the community receive balanced information from this development, their perception are changed among the rural communities of Idamdehe. Those who first agree with the plan, became hesitant and refused the development of geothermal energy.